First Aid in Efforts to Increase the Knowledge and Skills of Welder Workers at Project Santos Pt.X Batam City (HEALTH CARE: JURNAL KESEHATAN, 2025)
Abstrack: In an industrial environment, occupational safety and health are very important, especially for workers who work with welding when using fire source equipment and processes that can be dangerous, welding workers are very vulnerable to injuries and other dangers. Therefore, it is very important for welding workers to receive first aid training to be better prepared in emergency situations and maintain work safety. First aid training is also very important to reduce the number of injuries caused by work accidents. The type of analysis designed to test the possibility of a relationship arising from interactions between variables is quantitative analysis. This research uses a quantitative design with a cross-sectional approach, namely an approach that is temporary at a time and is not followed continuously over a certain period of time. Activities carried out include collecting data on dependent and independent variables. Based on the frequency distribution of first aid effectiveness, the majority of 24 respondents (60%) first aid training for welder workers was declared effective, and 16 respondents (40%) first aid training for welder workers was declared ineffective. Based on the Frequency Distribution of the Effect of First Aid knowledge, the majority of 24 respondents (60%) stated that first aid training for Welder workers had no effect, and 16 respondents (40%) stated that first aid training for Welder workers had an effect.